Detachment and successive re-attachment of multiple, reversibly-binding tethers result in irreversible bacterial adhesion to surfaces - Sjollema, Jelmer; van der Mei, Henny C.; Hall, Connie L.; Peterson, Brandon W.; de Vries, Joop; Song, Lei; Jong, Ed D. de; Busscher, Henk J.; Swartjes, Jan J. T. M. (Scientific reports, 2017)
Bacterial adhesion to surfaces occurs ubiquitously and is initially reversible, though becoming more irreversible within minutes after first contact with a surface. We here demonstrate for eight bacterial strains comprising four species, that bacteria adhere irreversibly to surfaces through multiple, reversibly-binding tethers that detach and successively re-attach, but not collectively detach to cause detachment of an entire bacterium. Arguments build on combining analyses of confined Brownian-motion of bacteria adhering to glass and their AFM force-distance curves and include the following observations: (1) force-distance curves showed detachment events indicative of multiple binding tethers, (2) vibration amplitudes of adhering bacteria parallel to a surface decreased with increasing adhesion-forces acting perpendicular to the surface, (3) nanoscopic displacements of bacteria with relatively long autocorrelation times up to several seconds, in absence of microscopic displacement, (4) increases in Mean-Squared-Displacement over prolonged time periods according to t α with 0 < α ≪ 1, indicative of confined displacement. Analysis of simulated position-maps of adhering particles using a new, in silico model confirmed that adhesion to surfaces is irreversible through detachment and successive re-attachment of reversibly-binding tethers. This makes bacterial adhesion mechanistically comparable with the irreversible adsorption of high-molecular-weight proteins to surfaces, mediated by multiple, reversibly-binding molecular segments.